2016
DOI: 10.1017/s2045796016000792
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparisons of increasing suicidal mortality rates for Koreans in the Republic of Korea and Korean Americans in the USA, 2003–2012

Abstract: Suicide in Korean Americans is higher than for other Asian Americans and follows temporal patterns more similar to Korea than the USA. Interventions to prevent suicide in Korean American populations, particularly among the elderly, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The findings of this study demonstrated that the methods of suicide attempt had an effect on the need for hospitalisation. Among the OECD countries, South Korea has the highest suicide rate, which is two times higher than that in the United States [ 22 ]. While suicide ranks as the 13th leading cause of life lost with 800,000 deaths worldwide annually [ 23 ], it is the 5th leading cause of death in South Korea [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study demonstrated that the methods of suicide attempt had an effect on the need for hospitalisation. Among the OECD countries, South Korea has the highest suicide rate, which is two times higher than that in the United States [ 22 ]. While suicide ranks as the 13th leading cause of life lost with 800,000 deaths worldwide annually [ 23 ], it is the 5th leading cause of death in South Korea [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study demonstrated that the methods of suicide attempt had an effect on the need for hospitalisation. Among the OECD countries, South Korea has the highest suicide rate, which is two times higher than that in the United States [22]. While suicide ranks as the 13th leading cause of life lost with 800,000 deaths worldwide annually [23] , it is the 5th leading cause of death in South Korea [24].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study demonstrated that the methods of suicide attempt had an effect on the need for hospitalization. Among the developed countries, South Korea has the highest suicide rate, which is two times higher than that in the United States [17]. The ED is an important point-of-care in the healthcare process for suicide attempters.…”
Section: Discussionmentioning
confidence: 99%